COMPLICATIONS OF LAPAROSCOPIC CHOLECYSTECTOMY: AN ANALYSIS OF 400 CONSECUTIVE CASES: Laparoscopic Cholecystectomy - Afzal, Muhammad; Rehman, Shafqat; Butt, Muhammad Qasim (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To analyze the complications of first 400 laparoscopic cholecystectomies (LC) for patients with symptomatic gall stone disease at a tertiary care hospital.Study Design: Quasi-experimental study.Place and Duration of Study: PNS Shifa Karachi and CMH Lahore, Pakistan from Nov 2009 to Jan 2013.Patients and Methods: A prospective analysis of complications occurring in first 400 consecutive laparoscopic cholecystectomies by a single consultant/unit at a tertiary care hospital was made. Out of total 421 patients presenting with symptomatic gall stone disease in a single unit, 21 cases that underwent open cholecystectomy were excluded from the study. Laparoscopic Cholecystectomies were performed using three port and four port technique and data including age, sex, diagnosis, number of trocar placements, conversion to open surgery and its reasons, operative time, post-operative hospital stay and complications was collected on personal computer and analyzed using Statistical package for social sciences (SPSS) version 13.Results: Total 400 patients were included in study with median age of 44years. Female to male ratio was 5.3: 1. Depending upon the preoperative diagnosis and laparoscopic findings, patients had diagnosis of Chronic cholecystitis / biliary colic 68.25%, acute cholecystitis 23.75%, empyema gall bladder 7.25%, gallstone pancreatitis 0.5% and mucocele gallbladder 0.25%. Median operating time was 30 min. Median hospital stay was 1days (range 1 – 20 days). Conversion rate was 1.25%. Postoperative complications included bleeding 0.5%, biliary peritonitis due to cystic duct leak 0.25%, biloma 0.25%, sub hepatic abscess 0.25%, subcutaneous fat necrosis right flank at drain site 0.25%, umbilical trocar site infection 2%, keloid at umbilical port site 0.25% and incisional hernia at umbilicus 0.25%. There was one hospital death due to myocardial infarction on 2nd post-operative day.Conclusion: Laparoscopic Cholecystectomy is associated with some serious complications which can be avoided with adequate training of surgeons as well as knowledge of mechanism of typical complications.